Analysis of 2-Year Survival Outcomes of Japanese Older Populations on Hemodiafiltration: A Propensity Score-Matched Study Based on Insurance Claims Data - Aziz Jamal; Akira Babazono; Ning Liu; Takako Fujita; Sung-a Kim; Yunfei Li (Kidney and Dialysis)
Despite the lack of evidence that suggests hemodiafiltration (HDF) offers a better survival outcome than standard hemodialysis (HD), the number of patients initiating HDF in Japan continues to rise. This study examined the temporal change in the number of HDF incidents, evaluated factors associated with all-cause mortality, and compared the mortality risk and survival time of patients on HDF with patients receiving standard HD in three sets of 2-year cohorts. The primary analyses included the insurance claims data of 460 HDF patients and propensity score-matched 903 standard HD patients who initiated dialysis therapy between 1 April 2012 and 31 March 2018. Patient follow-up was censored at the time of death or the end of the 2-year study period. The number of patients who initiated HDF and the proportion of all-cause mortality cases were evaluated. Additionally, the survival outcomes between propensity score-matched HDF and standard HD patient groups were compared throughout cohorts. The number of HDF patients increased throughout cohorts, but the proportions of mortality cases across cohorts slowly decreased. Adjusting for all study covariates, we observed that HDF patients had a lower mortality risk and longer survival time than patients on standard HD. This study supports the notion that HDF lowers all-cause mortality compared with standard HD in an incident dialysis population in Fukuoka Prefecture, Japan.